2023
DOI: 10.1111/1440-1681.13769
|View full text |Cite
|
Sign up to set email alerts
|

Rabeprazole destroyed gastric epithelial barrier function through FOXF1/STAT3‐mediated ZO‐1 expression

Abstract: Rabeprazole is a representative of proton pump inhibitors and widely used in antiulcer treatment. However, the effect of Rabeprazole on gut barrier function remains to be identified. In this study, we show that ZO-1 expression is decreased in patients receiving Rabeprazole by immunofluorescence (IF) analysis. Western blotting (WB) and real-time PCR (qPCR) results demonstrate that Rabeprazole treatment leads to a significant downregulation of ZO-1 expression through inhibition of the FOXF1/STAT3 pathway, leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The involvement of non-classical pathways of cellular pyroptosis and other pathways may exist in this pathologic process. Rabeprazole treatment regulates ZO-1 expression in the gastric mucosa via the forkhead box F1/signal and the transcription 3 pathway [32] . PPIs may differentially affect the mucosal barrier by altering the composition of the gut microbiota [33] .…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of non-classical pathways of cellular pyroptosis and other pathways may exist in this pathologic process. Rabeprazole treatment regulates ZO-1 expression in the gastric mucosa via the forkhead box F1/signal and the transcription 3 pathway [32] . PPIs may differentially affect the mucosal barrier by altering the composition of the gut microbiota [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more work about the function of PPI in gastrointestinal function has been reported. The previous studies from our lab have demonstrated that another PPI, rabeprazole, inhibited gastric epithelial cell proliferation, which was attributed to the inhibitory effect of Rabeprazole on Signal transducer and activator of transcription 3 (STAT3)-mediated glycolysis (Zhou et al, 2021), further work showed that rabeprazole inhibited cell pyroptosis, leading to decrease inflammatory reaction (Xie et al, 2021), and destroyed gastric barrier function by inhibition of FOXF1/STAT3-mediated ZO-1 expression (Yang et al, 2023). In addition to rabeprazole, we also demonstrated that omeprazole suppressed de novo lipogenesis in gastric epithelial cells by reducing fatty acid synthase and ATP citrate lyase expression (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 93%